Estudo dos efeitos do bloqueio da integrina αvβ3 por uma desintegrina RGD recombinante na cicatrização de hérnia incisional em ratos - Oliveira, Claudio Ricardo de (Universidade Federal de São Carlos, 2014)
Introduction: Incisional hernia (IH) is considered a connective tissue disease characterized by defective wound healing process, and it is found in high incidence after abdominal surgeries. Previous studies have shown that DisBa- 01 presents high-affinity to αvβ3, which can have wide therapeutic application and/or laboratorial in disorders related to collagen. Hypothesis: Considering the regulatory role of the vitronectin receptor, the αvβ3 integrin, in wound healing, we hypothesized that blocking this integrin would affect tissue repair. Objectives: To evaluate the DisBa-01 (a desintegrin RGD-recombinant by snake venom of Bothrops Alternatus) as a blockage of αvβ3 integrin on improvement of HI healing. Methods: IH was successfully induced in rats of Sham and DisBa-01 group. DisBa-01 group were treated with different doses (0.25; 0.5 and 1.0 mg/kg). A control group without surgery was included to analyze the surgery effects. Were evaluated the histology, zymography and gene expression of MMP-2, type I and III collagen and VEGF. Type 1A collagen were analysed by Western Blotting. Results: After 14 days, the presence of IH and hernia ring were observed in all sham-operated animals; in contrast, 100% of animals treated with 0.25 and 1.0 mg/kg of Disba-01 did not present visible signals of hernia and showed closed hernia rings. The surgery procedure strongly activated MMP-2 gene expression as well as its activity (P<0.05). Up-regulation of collagen 1 (col-1) and 3 (col-3) gene expression was also observed, DisBa-01 reduced the expression of col-I, however, did not affect col-III, while VEGF expression was down regulated at day14. In contrast, DisBa-01 significantly inhibited MMP-2 gene expression and its activity. Western Blotting analysis revealed the presence of Type1A collagen in all groups, however only DisBa-01 differed statistically of Control group. The thickness of the collagen layer in each of control group presented reduced. However, Sham and DisBa-01, there was a relative increase in all studied animals (P<0.05). Conclusion: These results indicate that αvβ3 integrin has an important role in the control of wound healing and its blockade modulate repair conditions, including IH. This information may be especially helpful for patients with recurrent IH.
Keywords: Hérnia; Abdomen; DisBa-01; Cicatrização de feridas; Ratos; Ventral hernial; Abdomen; Wound healing; Rats; CIENCIAS BIOLOGICAS::FISIOLOGIA